2021
DOI: 10.1002/dev.22147
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors, stress, hair cortisol, and white matter microstructure in children

Abstract: Socioeconomic disadvantage has been linked to increased stress exposure in children and adults. Exposure to stress in childhood has been associated with deleterious effects on cognitive development and well‐being throughout the lifespan. Further, exposure to stress has been associated with differences in brain development in children, both in cortical and subcortical gray matter. However, less is known about the associations among socioeconomic disadvantage, stress, and children's white matter development. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…Past studies have demonstrated a relationship between white matter development and socioeconomic factors, such as parental income, environmental stress and home context 14,19,21 . We began by attempting to replicate the results from past studies that observed univariate relationships between white matter and socioeconomic factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Past studies have demonstrated a relationship between white matter development and socioeconomic factors, such as parental income, environmental stress and home context 14,19,21 . We began by attempting to replicate the results from past studies that observed univariate relationships between white matter and socioeconomic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Intervention studies have shown that an individual's academic environment can drive measurable changes in brain structure and function 28,29,31 . However, it remains unclear the extent to which educational opportunities uniquely influence brain development above and beyond other socioeconomic factors 12,16,19 . Here we operationalize educational opportunity based on data from the Stanford Educational Data Archive (SEDA) 27 .…”
Section: Exploring the Relationship Between Educational Opportunity A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, animal studies suggest that both glucocorticoids and the GSH-antioxidant balance may play a role in modulating myelin maturation [ 42 , 43 ]. Several clinical studies report negative association between morning cortisol levels and neuroimaging indices of white matter microstructure such as fractional anisotropy (FA) [ 44 , 45 ], whereas others report developmental exposure to glucocorticoids and stress to be associated with increased FA [ 46 , 47 ]. Regarding the role of redox regulation, we previously reported a positive association between central levels of GSH in the prefrontal cortex measured by magnetic resonance spectroscopy, and structural and functional connectivity along the cingulum bundle in healthy young adults, suggesting that redox regulation supported by the GSH-redox cycle may be involved in white matter maturation [ 42 ].…”
Section: Introductionmentioning
confidence: 99%